Supported Social Enterprise: A Modified Social Welfare Organization. (April 2017) - Chan, Andrea; Ryan, Sherida; Quarter, Jack
This article presents a study of supported social enterprise, a hybrid organization that not only either employs or trains members of marginalized social groups, often on disability pensions and social assistance, but also has social welfare characteristics. These organizations sell services and goods, like other forms of social enterprise, but rely heavily on external support from government programs, foundations, and a parenting nonprofit. The article presents an empirical study using a survey and interviews of participants in these organizations from Ontario, Canada, and notes that even though they earn minimally from work in these organizations, they view the experience positively. The final discussion centers on the concept of supported social enterprise and raises the question as to whether such organizations should be viewed primarily as a form of social enterprise or as a modified form of social welfare organization.